2020
DOI: 10.1002/ange.202014167
|View full text |Cite
|
Sign up to set email alerts
|

Reduktion und Umlagerung eines Bor(I)‐Carbonylkomplexes

Abstract: Bei der Einelektronenreduktion eines durch eine cyclisches (Alkyl)(amino)carben (CAAC) stabilisierten Arylborylen‐Carbonylkomplexes erfolgt die Bildung eines dimeren Borylketyl‐Radikalanions, bedingt durch eine intramolekulare Arylmigration zum CO Kohlenstoffatom. Computergestützte Analyse liefert Hinweise auf eine radikalanionische [(CAAC)B(CO)Ar].− Zwischenstufe. Weiterführende Reduktion des entstandenen Komplexes liefert ein hoch nukleophiles (Boranyliden)methanolat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…The 1 H NMR spectrum shows a characteristic set of three vinylamino resonances in a 1 : 1 : 1 ratio at 8.01 (dd, NC H ), 4.35 (d, H cis ) and 3.81 (d, H trans ) ppm, with 3 J cis and 3 J trans coupling constants of 8.9 and 16.1 Hz, respectively. The solid‐state structure of 9 (Figure 5) confirms the migration of the Dip substituent from N1 to N3, as well as the tautomerization of the CMe to the allyl substituent, with a C2−C3 double bond of 1.324(4) Å. Migration of the Dip substituent from the CAAC nitrogen to the carbon atom of a boron‐bound ligand has only been observed within the radical anion [(CAAC Me )B(CO)(Tip)]⋅ − (Tip=2,4,6‐tri iso propylphenyl) [41] . The reaction likely proceeds via the formation of a tricoordinate acetonitrile adduct A , followed by tautomerization to a CAAC‐stabilized amino(vinylimino)borane B and finally Dip migration from the CAAC to the imino nitrogen atom (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR spectrum shows a characteristic set of three vinylamino resonances in a 1 : 1 : 1 ratio at 8.01 (dd, NC H ), 4.35 (d, H cis ) and 3.81 (d, H trans ) ppm, with 3 J cis and 3 J trans coupling constants of 8.9 and 16.1 Hz, respectively. The solid‐state structure of 9 (Figure 5) confirms the migration of the Dip substituent from N1 to N3, as well as the tautomerization of the CMe to the allyl substituent, with a C2−C3 double bond of 1.324(4) Å. Migration of the Dip substituent from the CAAC nitrogen to the carbon atom of a boron‐bound ligand has only been observed within the radical anion [(CAAC Me )B(CO)(Tip)]⋅ − (Tip=2,4,6‐tri iso propylphenyl) [41] . The reaction likely proceeds via the formation of a tricoordinate acetonitrile adduct A , followed by tautomerization to a CAAC‐stabilized amino(vinylimino)borane B and finally Dip migration from the CAAC to the imino nitrogen atom (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…N‐heterocyclic carbenes (NHCs) have proved to be effective ligands for the stabilization of main group element compounds, in which NHCs usually stay inert during reactions [24–28] . On the other hand, recent studies revealed that ring expansion and bond activation reactions of NHCs can also occur, resulting in the degradation of NHCs [29–36] . Herein, we report the synthesis and structural characterization of a NHC‐stabilized iminoborane 4 via exocyclic C−N activation of NHC.…”
Section: Introductionmentioning
confidence: 99%